(3EjKGQ GdMb Ydi GdNdb aj QO GdNdGaGJ Edi ePGgH GdMbs - (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s ((3eMeO Hf CMeO Hf YHO Gddg Hf jMji Hf MeRI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf Cced GdMeO Ydi LejY gOGjGJg heYGQag s
(3BNQgG (B:s
(3Ke CNJe gPG GdeNJUQ GdeHGQc HCfi CSJZaQ Gddg hCSCdg GdJLGhR Yfi hBNQ cdGei cChdg Cf GdMeO ddg QH GdYGdejf s
(3HBNQgG ebGHdJfG GdChdi SfI (B846s
(3hGdKGfjI SfI (B847 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B210s
Keywords: (3CUhd Gdabgs